COMPARATIVE BRAKING TESTS OF M1 CATEGORY VEHICLE - Ondrus, Jan (Doprava a spoje, 2009)
This contribution deals with problems of braking the automobile, specifically of category M1. It was carried out the measurement of braking deceleration of the vehicle Citro?n C6 by Correvit system under different conditions in three modes due to tyre inflation pressure. Test place was airport in the village of Rosina in Zilina. In the finish part of this contribution are presented results of performed measurement and its evaluation and comparison.